(3OjhGf GdZRjs - (3GdZRj , EHQGgje Hf YKeGf Hf eMeO GdcdHj GdGTgHj, CHh ESMGb CHh YKeGf,J (B524 (3g` s ((3eMeO Hf CHj SYjO Hf CHj efUhQ s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdhGLH, hYdi fHjg eMeO GdeNUhU HGdefGbH, aEf GdTYQ RHOI GdYQH hejOGf GdYQH, hbO LeYJ dg (B((3Cj GdhRjQ HgGA GdOjf(B) (3eeG bdJ ajg s
(3BNQgG (B:s
(3eGdc YQV JNGa hUeJg Cj WdGb JNGag YRH Cf cGfJ eGdgG SdH jO Lj aaj Ob QmCgG SdH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B44s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B167 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B762s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs